ANALISIS DAN PERANCANGAN HYBRID APPLICATION UNTUK NAVIGASI DAN PERTEMUAN - Richard Vinc Nicolay Santoso; Djunaidy Santoso (Jurnal Informatika dan Bisnis, 2015)
This research is motivated by the problem of how difficult is to plan a meeting and alse the differences between operating systems make developers hard to develop an application and user to get an application. Researcher apply the concept of a hybrid application to create an application using web technology so it can run on any operating system. Through a hybrid application, developer can target an application to a wider market and user can find these applications with ease. Researcher conduct direct observation, distributing questionnaires to the targeted respondents and conduct a literature review of the previous studies that have the same topic and a patent on the application of the current meetup application that had been circulated. Researcher also cite several books that discuss the development of mobile applications and hybrid applications. The findings that researcher get include of the difficulties felt by the user of meetup application that circulated such as application are incompatible with the operating system used, the absence of tracking features and not allowing members to add a reminder to the device’s calendar. Through a process of research that has researcher run and the application development process that has taken place, the researcher concluded that the application is able to simplify the process planning a meetup and members to attend the meeting.